2001
DOI: 10.1080/01140671.2001.9514160
|View full text |Cite
|
Sign up to set email alerts
|

Influence of honey bee (Apis mellifera) on kiwifruit pollination and fruit quality under Australian conditions

Abstract: The influence of honey bee (Apis mellifera L.) pollination of kiwifruit (Actinidia deliciosa (A.Chev.) C.F. Liang et A.R. Ferguson) under different pollination regimes (viz. honey bee supplementation, honey bee saturation in a cage with a single male cultivar, and honey bee exclusion) was investigated under Australian conditions during 1993/94 and 1995/96 seasons. Vines that had no access to honey bees had significantly (P 0.01) lower fruit set (24%) compared to honey bee supplementation (91%) and bee saturati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 25 publications
1
20
0
Order By: Relevance
“…Kiwifruit is one of 13 leading global food crops for which entomophilous pollination is essential (Klein et al 2007). Kiwifruit is dioecious, and insects are needed to transfer pollen from male to female vines because wind pollination is insufficient for a successful kiwifruit yield (Donovan and Read 1990;Costa et al 1993;Vaissiere et al 1996;González et al 1998;Howpage et al 2001;Pomeroy and Fisher 2002). Insects are needed not only for fruit set but also to obtain commercial fruit size because kiwifruit size is strongly correlated with seed number (Costa et al 1993;González et al 1998;Pomeroy and Fisher 2002), which depends on the number of pollen grains reaching the ovules.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kiwifruit is one of 13 leading global food crops for which entomophilous pollination is essential (Klein et al 2007). Kiwifruit is dioecious, and insects are needed to transfer pollen from male to female vines because wind pollination is insufficient for a successful kiwifruit yield (Donovan and Read 1990;Costa et al 1993;Vaissiere et al 1996;González et al 1998;Howpage et al 2001;Pomeroy and Fisher 2002). Insects are needed not only for fruit set but also to obtain commercial fruit size because kiwifruit size is strongly correlated with seed number (Costa et al 1993;González et al 1998;Pomeroy and Fisher 2002), which depends on the number of pollen grains reaching the ovules.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated the effectiveness of using managed honeybees (Apis mellifera ) (Vaissiere et al 1996;Howpage et al 2001, but see Clinch 1984;Costa et al 1993) and bumblebees (Bombus spp.) (Pomeroy and Fisher 2002) to pollinate kiwifruit, yet reliance on a single species for pollination is an inherently risky strategy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We put the nets over the flower buds before the onset of flowering. Leaves and plant parts with no flowers were left as much as possible outside the net bag to minimize any effects of the bag on the photosynthesis (Howpage et al 2001). As soon as flowers had wilted, we removed the nets, and the tagged plants were left to ripen in the field until harvest.…”
Section: Experimental Design and Yield Analysismentioning
confidence: 99%
“…Each seed is the result of a successful fertilisation by a single pollen grain. herefore production of an export quality kiwifruit requires that a large number of viable pollen grains are deposited on the stigmas of a female lower (Howpage et al 2001). Although kiwifruit lowers are fragrant, they do not produce nectar and therefore they are not very attractive to pollinating insects such as honey bees, yet pollination needs to occur in the relatively short period of time (ca 6 days) when the stigmas are receptive to pollen (Gonzalez et al 1995).…”
Section: Introductionmentioning
confidence: 99%